Evaluasi Kinerja Organisasi Dinas Pendidikan Kota Semarang - Retno Widowati; Nina Widowati; Rihandoyo Rihandoyo (Journal of Public Policy and Management Review, 2015)
This study aimed to describe supporting factors and inhibiting organizational performance and to evaluate the organizational performance of Semarang City Department of Education in achieving quality. The study used the theory of the factors that affect the performance of the organization. The factors that affect the performance of the organization used in the study include human resources; facilities and infrastructure; management information systems; cooperation; and leadership. This study used qualitative research method of descriptive. Based on the research results, factor that support the performance of the organization are human resources, cooperation and leadership whereas inhibiting factor are facilities and infrastructure; and management information systems. Organizational performance evaluation results indicate that the 9-year compulsory education targets have been met, the drop-out rate reached the national minimum servive standard, a decrease in the number of graduates, reduction in the number of teachers, reduction in the number of students repeating, decreasing dropout, an increase in the availability of the library, infirmary, computer rooms and laboratories, but a decrease in the availability of classrooms in the year 2013/2014. The suggestions given are fulfilling the availability of infrastructure needs, manage and utilize the education management system optimally, improve the education standard that is 12-year compulsory and seeks to reduce the children street in order to avoid dropping out of school, prepare for the exam to increase the number of the graduates and urged local governments to fulfilling the needs of theachers, do more focused on the construction of classrooms and repair the damaged